PENGEMBANGAN MEDIA CD INTERAKTIF MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI KELAS VII SMP NEGERI 6 SINGARAJA - Erni Suardani, Ketut (Universitas Pendidikan Ganesha, 2014)
The study aimed to: (1) design and implement the development of interactive CD Media of Technology Information and Comunication (ICT) subject for VII grade student ofSMPN 6 Singaraja. (2) To know the students respond toward imply the development ofinteractive CD Media of Technology Information and Comunication (ICT) subject for VII grade student of SMPN 6 Singaraja.The subject of the study was all student of VII B4 class of SMPN 6 Singaraja in theacademic year to 2009 / 2010, which consisted of 42 students. The study was researchdevelopment. The data were collected in the form of students respond toward the development of interactive CD Media. The instrument used in this study was questionnaire.The data of students respond and the data judges were analysed descriptively. The judge?s data were used for suggestion to improve the quality of interactive CD Media.The results of the study were interactive CD of ICT and the students respond towardthe development of interactive CD TIK. The result ranged at positive category 45%. The mean score of students respond was 64, 95 and it was categorized positiv